MyD88-mediated signals induce the bactericidal lectin RegIIIγ and protect mice against intestinal Listeria monocytogenes infection - Brandl, Katharina (The Rockefeller University Press, 2007)
Listeria monocytogenes is a food-borne bacterial pathogen that causes systemic infection by traversing the intestinal mucosa. Although MyD88-mediated signals are essential for defense against systemic L. monocytogenes infection, the role of Toll-like receptor and MyD88 signaling in intestinal immunity against this pathogen has not been defined. We show that clearance of L. monocytogenes from the lumen of the distal small intestine is impaired in MyD88(−/−) mice. The distal ileum of wild-type (wt) mice expresses high levels of RegIIIγ, which is a bactericidal lectin that is secreted into the bowel lumen, whereas RegIIIγ expression in MyD88(−/−) mice is nearly undetectable. In vivo depletion of RegIIIγ from the small intestine of wt mice diminishes killing of luminal L. monocytogenes, whereas reconstitution of MyD88-deficient mice with recombinant RegIIIγ enhances intestinal bacterial clearance. Experiments with bone marrow chimeric mice reveal that MyD88-mediated signals in nonhematopoietic cells induce RegIIIγ expression in the small intestine, thereby enhancing bacterial killing. Our findings support a model of MyD88-mediated epithelial conditioning that protects the intestinal mucosa against bacterial invasion by inducing RegIIIγ.